XiaoEr LianHuaQinqGan alleviates viral pneumonia in mice infected by influenza A and respiratory syncytial viruses - Wenyan Li; Tongtong Li; Chi Zhao; Tao Song; Yao Mi; Zhang Chuangfeng; Yunlong Hou; Zhenhua Jia (Taylor & Francis Group, 2022)
AbstractContext Xiaoer lianhuaqinqgan (XELH), developed based on Lianhua Qingwen (LHQW) prescription, contains 13 traditional Chinese medicines. It has completed the investigational new drug application to treat respiratory viral infections in children in China.Objective This study demonstrates the pharmacological effects of XELH against viral pneumonia.Materials and methods The antiviral and anti-inflammatory effects of XELH were investigated in vitro using H3N2-infected A549 and LPS-stimulated RAW264.7 cells and in vivo using BALB/c mice models of influenza A virus (H3N2) and respiratory syncytial virus (RSV)-infection. Mice were divided into 7 groups (n = 20): Control, Model, LHQW (0.5 g/kg), XELH-low (2 g/kg), XELH-medium (4 g/kg), XELH-high (8 g/kg), and positive drug (20 mg/kg oseltamivir or 60 mg/kg ribavirin) groups. The anti-inflammatory effects of XELH were tested in a rat model of LPS-induced fever and a mouse model of xylene-induced ear edoema.Results In vitro, XELH inhibited the pro-inflammatory cytokines and replication of H1N1, H3N2, H1N1, FluB, H9N2, H6N2, H7N3, RSV, and HCoV-229E viruses, with (IC50 47.4, 114, 79, 250, 99.2, 170, 79, 62.5, and 93 μg/mL, respectively). In vivo, XELH reduced weight loss and lung index, inhibited viral replication and macrophage M1 polarization, ameliorated lung damage, decreased inflammatory cell infiltration and pro-inflammatory cytokines expression in lung tissues, and increased the CD4+/CD8+ ratio. XELH inhibited LPS-induced fever in rats and xylene-induced ear edoema in mice.Conclusion XELH efficacy partially depends on integrated immunoregulatory effects. XELH is a promising therapeutic option against childhood respiratory viral infections.